(untitled) (The Pakistan Development Review, 2025)
Internet is the most revolutionary technology that impacts individuals, economy and culture of any society. It has been shaping a major paradigm shift in business strategies. Entrepreneur and businessmen are able to reduce both the production and transaction costs, foster spread of new ideas and enhance productivity, Manyika & Roxburgh (2010). The impacts are widespread on promoting market efficiency, Dolata (2018).